ANALISIS PERILAKU PEMBELIAN BUAH DI PERDESAAN DAN PERKOTAAN - Retnaningsih, Retnaningsih; Parhati, Rahmi; Simanjuntak, Megawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2013)
This study aimed to analyze the differences of purchasing behavior of fruit in rural and urban areas. In addition, this study also aimed to analyze the influence of family characteristics and knowledge on the purchasing behavior of the fruit. The study was conducted in the Panaragan Village (Bogor City) and Cihideung Ilir village (Bogor Regency) and involved a number of respondents that were 99 housewives that were selected randomly. Data were collected by interviews and analyzed by descriptive analysis, different test, and regression test. The results showed that the housewives of rural areas had the knowledge and purchasing behavior that were significantly different than in the urban’s housewives. Purchasing behavior based on the type of fruit, fruit origin, frequency of purchase, and the purchase amount of fruit were affected by age and length of education. In addition, income and knowledge also influenced the purchasing behavior of fruit housewives based on the origin of the fruit.